2020
DOI: 10.1364/oe.403556
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective optical trapping of chiral nanoparticles using a transverse optical needle field with a transverse spin

Abstract: Since the fundamental building blocks of life are built of chiral amino acids and chiral sugar, enantiomer separation is of great interest in plenty of chemical syntheses. Light-chiral material interaction leads to a unique chiral optical force, which possesses opposite directions for specimens with different handedness. However, usually the enantioselective sorting is challenging in optical tweezers due to the dominating achiral force. In this work, we propose an optical technique to sort chiral specimens by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…[9] Compared to CD and complex chemical methods, [10][11][12] optical force-based methods with less invasiveness and higher efficiency have developed into a topic of active research. [13][14][15][16][17][18][19][20][21][22][23][24][25] There are many methods to generate the optical forces related to chirality, including the chirality-dependent lateral optical forces (LOFs) emerging from the interaction of the spin angular momentum with chiral particles, [13,14] the optical chiral forces induced by circularly polarized beams [16,21] and vector beams. [17,18,20] Especially, the optical enantioselective trap allows to simultaneously confine a pair of enantiomers of opposite chirality at two different positions, achieved by beams of radially varying polarization states [18] and vector Lissajous beams.…”
Section: Introductionmentioning
confidence: 99%
“…[9] Compared to CD and complex chemical methods, [10][11][12] optical force-based methods with less invasiveness and higher efficiency have developed into a topic of active research. [13][14][15][16][17][18][19][20][21][22][23][24][25] There are many methods to generate the optical forces related to chirality, including the chirality-dependent lateral optical forces (LOFs) emerging from the interaction of the spin angular momentum with chiral particles, [13,14] the optical chiral forces induced by circularly polarized beams [16,21] and vector beams. [17,18,20] Especially, the optical enantioselective trap allows to simultaneously confine a pair of enantiomers of opposite chirality at two different positions, achieved by beams of radially varying polarization states [18] and vector Lissajous beams.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of sorting enantiomers using an all-optical method would have a profound impact on the drug and pharmaceutical industries, and as such there has been a substantial number of studies looking at enantioselective trapping schemes. These have predominantly involved using an unstructured laser source [8][9][10][11] and/or plasmonic enhancement systems [12][13][14][15][16][17][18][19][20][21][22][23][24] , though there have been a handful of studies employing structured light 20,[25][26][27][28][29] . Optical vortices are inherently chiral, their OAM per photon is where  is known as the topological charge.…”
Section: Introductionmentioning
confidence: 99%
“…19 In recent years, several studies have demonstrated the promise of plasmonic optical trapping and transport. [20][21][22] For example, Kai Wang and his colleagues had proposed a method to trap and rotate the nanoparticles. In his letter, although the gold pillars can be used to trap and rotate the nanoparticles, but the nanoparticles just rotate around the gold pillars, not a long distance transport.…”
Section: Introductionmentioning
confidence: 99%